Investment Objectives of Mutual Fund Investors - Thomas, Basil John (International Journal of Economics, Business and Management Studies, 2020)
The investment objective of Mutual fund investors is the first and foremost aspect for a mutual fund investor when investment decisions are made. Investment objective is referred to as a collective sum of all the factors considered by an investor while investing in to a particular avenue where he needs to capitalize reaping desired returns in future. Through this paper the author analyses the objectives of mutual fund investors by considering various factors such as time horizon and demographic profile to evaluate their financial behaviour. For this a sample of 400 individual investors has been selected to analyse the objectives of mutual fund investors, weighted score ranking of objectives and its association with time horizon and demographic profile of investors. The current research revealed that the investment objectives of mutual fund investors vary with their time horizon of investment where as it doesn’t vary with demographic features.